Influence of leadership, motivation, and training on the performance of Periuk District Office employees - Devi Fransisca; Frida Aprillia (Junal Ilmu Manajemen, 2023)
In a study entitled "The Influence of Leadership, Motivation, and Training on the Performance of Periuk District Office Employees". Bina Sarana Informatics University, Management Study Program, Department of Economics and Business. Aims to determine the effect of Leadership, Motivation, and Training on the Performance of Periuk District Office Employees, Tangerang City. This study uses a quantitative method with the type of research Field research. Data collection techniques using a questionnaire in the form of a questionnaire. The data analysis technique used multiple linear regression analysis through the SPSS 25 application. The population used was all employees of the Periuk sub-district office of 40 people by taking a total sample of 40 people. As for the results of this study, the results of the t test partially determine that there is a statistically significant relationship between leadership ability (X1) and employee performance (Y), then the results of the t test partially determine there is no partially significant relationship to employee performance in motivation, but training has little or no effect on employee performance.